ISRA’ILIYYAAT DALAM MENCERITAKAN KISAH-KISAH AL-QUR’AN - Ahmad Zarnuji (Institut Agama Islam Ma'arif NU (IAIMNU) Metro Lampung, 2016)
Islam is a religion falsifies revealed to the prophet Muhammad by the angel Gabriel intermediary. Al-Qur'an as the holy book of Islam is the only heavenly books that God promised the integrity and authenticity of the truth until the end of time. Style disclosure Qur'an related to the stories of the previous race are global. That is, in expressing a particular event Qur'an does not specify about the time, the scene and the names of the characters involved. Therefore, in the narration of the stories of the commentators are not always taken from the people of Islam, even some narration taken from non-Islamic people, both from the Jews and Christian. Because it feared the reports are affected by the beliefs they hold the end of the century exegetes tried to distill the entire narration that comes from the Jews and the Christians.